Pengaruh Product Features, Advertising Attractiveness, dan Celebrity terhadap Keputusan Penggunaan Platform Media Sosial Tiktok - Dyah Putri Utami; Kabul Trifiyanto (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
This study aims to determine the effect of product features, advertising attractiveness and celebrity on decisions to use the TikTok social media platform. The data collection technique in this study was carried out by distributing questionnaires to 100 respondents using the TikTok social media platform using purposive sampling as a sampling technique. The data analysis technique used in this research is descriptive analysis and statistical analysis which includes instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test using the SPSS 25 for windows program. The results of this study indicate that the product features, advertising attractiveness, and celebrity variables partially and simultaneously have a significant effect on decisions to use the TikTok social media platform. Keywords: Product features; advertising attractiveness; celebrity; usage decision.